2006
DOI: 10.1111/j.1460-2466.2006.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Little Words That Matter: Discourse Markers “So” and “Oh” and the Doing of Other-Attentiveness in Social Interaction

Abstract: The article presents an analysis of actual, recorded social interactions between close familiars with the goal to describe discursive practices involved in showing engagement with the other party, or other‐attentiveness. Focusing on the deployment of the discourse markers “so” and “oh” in utterances that launch new conversational topics, the article demonstrates that “so” overwhelmingly prefaces other‐attentive topics, whereas “oh” prefaces self‐attentive topics. We consider the interactional implications of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(119 citation statements)
references
References 47 publications
5
106
0
2
Order By: Relevance
“…Johnson (2002) described the use of so for prefacing questions in police interviews and argued that it is used to focus the participants' attention on the interview's agenda. Most recently, Bolden (2006) argued that, when introducing new topics in conversation, so can be used to highlight the speaker's involvement in the addressee's life world by marking the topic as pending or incipient.…”
Section: So … What Is So?mentioning
confidence: 99%
“…Johnson (2002) described the use of so for prefacing questions in police interviews and argued that it is used to focus the participants' attention on the interview's agenda. Most recently, Bolden (2006) argued that, when introducing new topics in conversation, so can be used to highlight the speaker's involvement in the addressee's life world by marking the topic as pending or incipient.…”
Section: So … What Is So?mentioning
confidence: 99%
“…It has been suggested that transitions can be identifi ed thanks to a number of linguistic markers. A wide array of markers of topic structure have been proposed in the literature: a concord of agreements and/or pauses (Maynard, 1980), existential structures (Berthoud, 1996;Geluykens, 1993), phatics and interjections (Berthoud & Mondada, 1995), dislocations (Grobet, 2002), cle s (Grobet, 2002), discourse markers (Horne et al, 2001) such as so (Bolden, 2006), new referents (Keenan Ochs & Schieff elin, 1976), etc. As far as prosodic cues are concerned, pitch parameters such as higher onsets (Nakajima & Allen, 1993), more range variation (Zellers, 2013) and fundamental equency peaks (Swerts & Geluykens, 1994) have been identifi ed for new topics.…”
mentioning
confidence: 99%
“…Indeed well very commonly prefaces topic shifts that initiate talk focusing on the speaker's own experiences or concerns. No less than 74% of the topic shift cases examined for this project have this self-attentive character, while only 19% are other-attentive and directly inquire into the recipient's experience or circumstances (Bolden, 2006).…”
Section: Topic Shiftsmentioning
confidence: 99%